Activities of Daily Living pada Lansia di Rojinhome Toyomi Urasoe-Shi Okinawa Jepang - Anastasia Mahtiara; Noor Rochmah Ida Ayu Trisno Putri; Etika Dewi Cahyaningrum (Universitas Harapan Bangsa, 2021)
Decreased body function in the elderly which can cause the physical condition of the elderly to change from time to time and the reduced muscle strength of the elderly can cause their daily living activities to be disrupted. Changes in social life in the elderly, inadequate economy, their liveliness in life will decrease so that their daily living activity (ADL) will change and may not have the enthusiasm to live their life. The purpose of this study was to describe the activities of daily living in the elderly at Rojinhome Toyomi Urasoe-Shi Okinawa, Japan. This research is a quantitative descriptive research. Determination of the sample using accidental sampling technique. The results showed that the elderly at Rojinhome Toyomi Ura-Soe Okinawa, Japan were mostly in the old age category (75 - 90 years) (72.2%). The elderly at Rojinhome Toyomi Ura-Soe Okinawa, Japan are mostly male (55.6%). The elderly at Rojinhome Toyomi Ura-Soe, Okinawa, Japan, most of the level of independence has a partial dependence in carrying out daily activities (66.7%).